2018
DOI: 10.1111/1468-0009.12312
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of the Health Care Industry: Curb Your Enthusiasm?

Abstract: We need to be patient in expecting system improvements from ongoing changes in provider payment and organization. We also may need to look for improvements in other areas of the economy or to accept and accommodate prospects of modest improvements over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
67
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 107 publications
1
67
0
Order By: Relevance
“…For example, a recent descriptive study by Burns and Pauly (2018) found that efforts to create financial incentives and efforts to create new provider organizations (such as alternative payment models, accountable care organizations, and patientcentered medical homes) have had a weak impact on quality and cost. For example, a recent descriptive study by Burns and Pauly (2018) found that efforts to create financial incentives and efforts to create new provider organizations (such as alternative payment models, accountable care organizations, and patientcentered medical homes) have had a weak impact on quality and cost.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…For example, a recent descriptive study by Burns and Pauly (2018) found that efforts to create financial incentives and efforts to create new provider organizations (such as alternative payment models, accountable care organizations, and patientcentered medical homes) have had a weak impact on quality and cost. For example, a recent descriptive study by Burns and Pauly (2018) found that efforts to create financial incentives and efforts to create new provider organizations (such as alternative payment models, accountable care organizations, and patientcentered medical homes) have had a weak impact on quality and cost.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…Similarly, the simplest alternative explanation for the long absence of large multispecialty groups is that economies of scale and scope in the delivery of physician services are modest (Goldsmith et al., ; Burns and Pauly, ). However, this explanation is hard to square with the observation that such groups have managed to thrive in some local markets, but not others .…”
Section: Introductionmentioning
confidence: 99%
“…Medical care in the United States has been historically delivered by practitioners operating out of their own offices or as attendings in hospitals (Starr, ; Robinson, ), and although it still commonly is (Burns, Goldsmith, and Sen, ; Baker, Bundorf, and Royalty, ), a rapidly growing percentage of physicians are operating in large groups organized by nonphysician owners (see Burns and Pauly, , for a review of physician models of practice organization).…”
mentioning
confidence: 99%
See 2 more Smart Citations